2018
DOI: 10.2302/kjm.2018-0002-ir
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Therapy for Patients with Congenital Heart Disease

Abstract: Congenital heart disease (CHD) is the most common birth defect, affecting 1 in 100 babies. Among CHDs, single ventricle (SV) physiologies, such as hypoplastic left heart syndrome and tricuspid atresia, are particularly severe conditions that require multiple palliative surgeries, including the Fontan procedure. Although the management strategies for SV patients have markedly improved, the prevalence of ventricular dysfunction continues to increase over time, especially after the Fontan procedure. At present, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Congenital heart disease is the most common birth defect, which is characterized by structural and functional abnormalities of the blood vessels caused by genetic and environmental factors. 17,18 Children with CHD have aberrant haemodynamics, including cyanosis, PHA and abnormalities of the vertebral artery, which in turn lead to serious complications such as arrhythmias, cardiac dysfunction or heart failure. 19,20 Several blood biomarkers have been proposed for the diagnosis and prognosis of cardiovascular disease (CVD).…”
Section: Discussionmentioning
confidence: 99%
“…Congenital heart disease is the most common birth defect, which is characterized by structural and functional abnormalities of the blood vessels caused by genetic and environmental factors. 17,18 Children with CHD have aberrant haemodynamics, including cyanosis, PHA and abnormalities of the vertebral artery, which in turn lead to serious complications such as arrhythmias, cardiac dysfunction or heart failure. 19,20 Several blood biomarkers have been proposed for the diagnosis and prognosis of cardiovascular disease (CVD).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that stem cells are present in the perivascular regions of various tissue types including the myocardium. Because of their intrinsic properties, they are able to secrete different angiogenic factors 78 which can increase myocardial angiogenesis, replace injured myocardium and improve myocardial function 79 . Clinical trials for stem cell therapy in CHD are mostly carried out in patients with single ventricle circulation, as can occur with HLHS.…”
Section: Reviewmentioning
confidence: 99%
“…Stem cell therapy could become a potential option to this which is why research has become recently highly anticipated. This stems further research for stem cell therapy and the idea of an alternative option to avoid heart transplantation [21]. The three consecutive surgeries: Norwood, Glenn and Fontan, are performed within the first few weeks of birth, the second between 4 to 6 months and the third within the first 4 years.…”
Section: Current Treatment For Congenital Heart Defectsmentioning
confidence: 99%
“…Particularly, research has demonstrated the injection of cardiomyocyte-like cells generated from iPSCs on MI animal models and shown that the iPSCs are able to integrate with the cardiac tissue and thus improve cardiac function [21]. One report demonstrated the generation of iPS cell-derived cardiomyocyte sheets and proved that these cells exhibit contraction and relaxation in vivo with the myocardium [61].…”
Section: Preclinial Studies Using Induced Pluripotent Stem Cellsmentioning
confidence: 99%